Holy Sci-fi! : where science fiction and religion intersect - Nahin, Paul J., 1940- (Springer, 2014)
Can a computer have a soul? Are religion and science mutually exclusive? Is there really such a thing as free will? If you could time travel to visit Jesus, would you (and should you)? For hundreds of years, philosophers, scientists and science fiction writers have pondered these questions and many more. In Holy Sci-Fi!, popular writer Paul Nahin explores the fertile and sometimes uneasy relationship between science fiction and religion. With a scope spanning the history of religion, philosophy and literature, Nahin follows religious themes in science fiction from Feynman to Foucault and from Asimov to Aristotle. An intriguing journey through popular and well-loved books and stories, Holy Sci-Fi! shows how sci-fi has informed humanity's attitudes towards our faiths, our future and ourselves. -- Resumé vydavatele
Keywords: vědecko-fantastická literatura; literatura a náboženství; science fiction; literature and religion